2015
DOI: 10.1080/17535069.2015.1011423
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of self-managed co-housing initiatives in France

Abstract: Defining what is understood as habitat participatif (participative or co-housing) in France comes up against regulatory ambiguities and a diversity of regional contexts and micro-local situations. Taking as its starting point a survey carried out in the city of Grenoble, which has a long tradition of cooperation and participatory politics, the article analyzes this diversity to identify the common characteristics of co-housing projects and to attempt to define an 'ideal type'. The cases are described in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 7 publications
0
13
0
4
Order By: Relevance
“…Co-housing initiatives remain the most popular projects among degrowth scholars. However, many studies have already shown the ambiguous socio-spatial implications of these intentional communities, not least that despite their aspirations to achieve a socially mixed structure, co-housing inhabitants are predominantly well-educated, middle-income households (Bresson and Denefle 2015;Lang, Carriou, and Czischke 2020). Although intentional communities have been perceived in many contexts as opportunities for vulnerable areas, the predominant social homogeneity of self-chosen neighbourhoods has often coincided with intensified segregation or gentrification (Holm 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-housing initiatives remain the most popular projects among degrowth scholars. However, many studies have already shown the ambiguous socio-spatial implications of these intentional communities, not least that despite their aspirations to achieve a socially mixed structure, co-housing inhabitants are predominantly well-educated, middle-income households (Bresson and Denefle 2015;Lang, Carriou, and Czischke 2020). Although intentional communities have been perceived in many contexts as opportunities for vulnerable areas, the predominant social homogeneity of self-chosen neighbourhoods has often coincided with intensified segregation or gentrification (Holm 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lietaert (2010) and Hagbert (2020) argue that the lifestyle of co-housing residents does not automatically reduce their environmental footprint and activities differ considerably from project to project. However, many studies have already illustrated issues related to the socio-spatial justice implications of these intentional communities, not least that despite their aspirations to achieve a socially mixed structure, co-housing inhabitants are predominantly well-educated, middle-income households (Bresson and Denefle 2015;Lang, Carriou, and Czischke 2020). Although those in the sector and especially activists hardly consider themselves "gentrifiers", critical research is ambivalent, pointing out that in owner-occupied middle-class projects, it is hardly possible to plan the social mix or to encourage the co-use of space.…”
Section: Intentional Communities and The Degrowth Agendamentioning
confidence: 99%
“…The scholarly literature on various types of collaborative housing contains informative and insightful contributions covering one or more relevant cases from Europe, North America, Asia and Australia (e.g. Bresson and Denéfle 2015;Chiodelli and Baglione 2014;Fromm 2012;Ganapati 2010;Hojer Bruun 2012;Jarvis 2015;Vestbro and Horelli 2012;Tummers 2015bTummers , 2016Crabtree 2018;Jakobsen and Larsen 2018;Moore 2018;Thompson 2018). In the following, we draw on this empirical work in our discussion of the concept and social mechanisms of CSH.…”
Section: Empirical and Theoretical Foundationsmentioning
confidence: 99%
“…environmental sustainability, design aspects and social contact, amongst others). Nonetheless, in the current post-recession and austerity context in Europe, 'affordability' and 'social inclusion' feature as new driving forces in many cases (Bresson & Den efle, 2015;Carriou, 2012;Chatterton, 2013). This marks a departure from the often 'middle-class' character attributed to these initiatives in the past, most notably co-housing projects.…”
Section: Introductionmentioning
confidence: 99%